How cells channel their stress: Interplay between Piezo1 and the cytoskeleton. (November 2017) - Nourse, Jamison L.; Pathak, Medha M.
Highlights: Ion channels are unique transducers of mechanical force. The Piezo1 channel converts mechanical cues into electrical and biochemical signals. Piezo1 transduces outside-in as well as inside-out mechanical forces. The cytoskeleton modulates Piezo1 activation in complex ways. Piezo1 activity affects cytoskeletal organization and dynamics. Abstract: Cells constantly encounter mechanical stimuli in their environment, such as dynamic forces and mechanical features of the extracellular matrix. These mechanical cues are transduced into biochemical signals, and integrated with genetic and chemical signals to modulate diverse physiological processes. Cells also actively generate forces to internally transport cargo, to explore the physical properties of their environment and to spatially position themselves and other cells during development. Mechanical forces are therefore central to development, homeostasis, and repair. Several molecular and biophysical strategies are utilized by cells for detecting and generating mechanical forces. Here we discuss an important class of molecules involved in sensing and transducing mechanical forces – mechanically-activated ion channels. We focus primarily on the Piezo1 ion channel, and examine its relationship with the cellular cytoskeleton.